The Dominant Negative IQGAP1(IR-WW) Domain as a Potential Therapy in Brain Cancer - Osman, Mahasin (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.